Single‐Cell Transcriptome Profiling Reveals Multicellular Ecosystem of Nucleus Pulposus during Degeneration Progression. Issue 3 (26th November 2021) - Tu, Ji; Li, Wentian; Yang, Sidong; Yang, Pengyi; Yan, Qi; Wang, Shenyu; Lai, Kaitao; Bai, Xupeng; Wu, Cenhao; Ding, Wenyuan; Cooper‐White, Justin; Diwan, Ashish; et al.
Abstract: Although degeneration of the nucleus pulposus (NP) is a major contributor to intervertebral disc degeneration (IVDD) and low back pain, the underlying molecular complexity and cellular heterogeneity remain poorly understood. Here, a comprehensive single‐cell resolution transcript landscape of human NP is reported. Six novel human NP cells (NPCs) populations are identified by their distinct molecular signatures. The potential functional differences among NPC subpopulations are analyzed. Predictive transcripts, transcriptional factors, and signal pathways with respect to degeneration grades are explored. It is reported that fibroNPCs is the subpopulation for end‐stage degeneration. CD90+NPCs are observed to be progenitor cells in degenerative NP tissues. NP‐infiltrating immune cells comprise a previously unrecognized diversity of cell types, including granulocytic myeloid‐derived suppressor cells (G‐MDSCs). Integrin α M (CD11b) and oxidized low density lipoprotein receptor 1 (OLR1) as surface markers of NP‐derived G‐MDSCs are uncovered. The G‐MDSCs are found to be enriched in mildly degenerated (grade II and III) NP tissues compared to severely degenerated (grade IV and V) NP tissues. Their immunosuppressive function and alleviation effects on NPCs' matrix degradation are revealed in vitro. Collectively, this study reveals the NPC‐type complexity and phenotypic characteristics in NP, thereby providing new insights and clues for IVDD treatment. Abstract : Low back pain is a common and debilitating condition with degeneration of the nucleus pulposus (NP) as the main cause. Here, human NP tissues with progressive degeneration grades are profiles, and a precise atlas of NP cells (NPCs) and immunocytes is constructed. The dynamics of NPC heterogeneity at the mRNA level during IVDD is characterized. These findings may aid the understanding of molecular complexity and cellular heterogeneity in intervertebral disc degeneration.